Out of Hospital Cardiac Arrest: A Current Review of the Literature that Informed the 2015 American Heart Association Guidelines Update - Milan, Melissa (Curr Emerg Hosp Med Rep, 2016)
Out-of-Hospital cardiac arrest affects over 300,000 individuals in the US per year and is the third leading cause of death for Americans. Given the extent of this public health problem, investigations are ongoing to improve upon outcomes for patients who suffer cardiac arrest. In 2015, the American Heart Association issued an update to the 2010 Cardiopulmonary and Emergency Cardiovascular Care Guidelines.(1) In this manuscript, we reviewed the literature that informed the major changes to the guidelines and present a concise review of the current literature that informs how patients who suffer a cardiac arrest are cared for in the pre-hospital, emergency department and in-hospital environment. Additionally, the new AHA guideline on Maternal Resuscitation will also be described.